Activities and Roles of Older Adults After Retirement: A Review-Based Analysis of Active Ageing - Corman, Sorina; Zamfirescu-Mareș, Dana (European Journal of Applied Sciences, 2026)
Population ageing and the extension of the post-retirement period have transformed retirement into a complex stage of life, with significant implications for quality of life, psychological well-being and the maintenance of social roles among older people. This review-based study examines theoretical perspectives that explain the relationship between activity, retirement and quality of life, identifies the main types of activities engaged in by older adults after retirement, and highlights the key factors influencing life satisfaction and the preservation of social roles in this stage of life. The literature analysis underscores the central role of activity, continuity and role theories, complemented by successful ageing models, active ageing perspectives and the life course approach, in explaining how social, productive and symbolic engagement contributes to the well-being of the elderly. Diverse typologies of post-retirement activities are identified, including paid work or self-employment, volunteering, leisure pursuits, physical activity, social and community involvement, educational, religious and personal development activities, each exerting differentiated effects on quality of life depending on context and individual meaning. The findings emphasize that life satisfaction and the maintenance of social roles after retirement are shaped by a complex constellation of individual, psychological, relational, economic and structural factors, with social participation, financial security, psychological resilience, social support and access to community opportunities playing essential roles. The conclusions highlight the need for integrative frameworks and public policies tailored to the diversity of pensioners, aimed at supporting active, healthy and fulfilling ageing.